Microsoft Dynamics CRM 2011 cookbook : includes over 75 incredible recipes for deploying, configuring, and customizing your CRM application - Bhattacharya, Dipankar (Packt Publishing, 2013)
This is a Cookbook with recipes aimed at all levels with lots of practical walkthroughs for virtualization techniques. This book is great for Dynamics CRM 2011 professionals who have a beginner level understanding of the system and are looking to get a good grounding in how to deploy, maintain, configure, and customize a Dynamics CRM 2011 application efficiently. It's assumed that the reader has a basic level understanding of IT infrastructure topologies along with functional knowledge of Dynamics CRM 2011 Sales, Marketing, and Services modules.